Distributional effects of public education transfers in seven European countries - Tim Callan; Tim Smeeding; Panos Tsakloglou (The Economic and Social Research Institute (ESRI), 2007)
Empirical studies of inequality and poverty are usually based on disposable cash incomes, disregarding incomes in-kind (non-cash incomes). Since individuals also derive utility from the consumption of goods and services provided in-kind monetary income is not always a good indicator of an individual's utility or 'command over resources'. Thus, distributional analysis based on cash incomes may be seriously biased. Inclusion of non-cash incomes (arising from private sources or from public provision of services such as health, housing and education) may allow for better targeting and allocation of resources in fighting poverty and social exclusion. The present paper focuses on non-cash incomes arising from publicly provided education in seven European countries (Belgium, Germany, Greece, Italy, Ireland, the Netherlands and the UK), as part of a broader research project (AIM-AP Accurate Income Measurement for the Assessment of Policy) investigating the distributional implications of including elements of non-cash income in the measurement of wider resources. In all countries under examination public education transfers account for a considerable proportion of the total transfers of the state to the citizens. The paper uses static incidence analysis under the assumption that public education transfers do not create noticeable externalities, combining the information of existing nationwide income surveys with external information on spending per student in particular levels of the education system. In all countries public education transfers are found to reduce aggregate inequality. These effects are driven by the impact of primary and, especially, secondary education transfers at the time of their receipt and assuming benefits are valued at cost by recipients. In a static framework, transfers in the field of tertiary education appear to have a small distributional impact while the size and the sign of this impact depend on the treatment of tertiary education students living away from the parental home.
Keywords: 330; Öffentliche Bildungsausgaben; Verteilungswirkung; Belgien; Deutschland; Griechenland; Italien; Irland; Niederlande; Großbritannien